THE IMPACT OF THE RECIPROCAL RELATIONSHIP BETWEEN EXCHANGE RATES AND INTEREST RATES ON THE BOND MARKET USING THE SVAR MODEL FOR CHINA FOR THE PERIOD FROM (2000-2020) - Idrees, Noralhuda; Nehme, Samir (Humanities Journal of University of Zakho, 2024)
This study aims to illustrate the effect of the reciprocal relationship between the exchange rates and interest rates on the bond market by using the SVAR model for China during (2000 -2020), this is to analyze and measure the relationship between exchange rates and interest rates and showing their impact through changes in the bond index and monitoring the changes that occur in their traded prices in the financial markets. This study is based on three standard model estimations. The first model includes the effect of interest rates and inflation on the exchange rates. The second model shows the effect of the exchange rates and money supply on the interest rate. The third model includes the effect of exchange and interest rates on the bond index. The Structural Vector Auto Regression Model (SVAR) was used to test the long-term relationship between the variables of the study, in addition to the variance Decomposition analysis and the analysis of the Impulse response functions (IRF). The results showed that the reciprocal relationship between the exchange rates and interest rates is a positive inverse relationship, and the effect is in both directions. In other words, when the prevailing interest rate rises in the country, it leads to an appreciation in the value of the currency due to the increase in demand for the currency of that country, resulting in a depreciation in its exchange rate and conversely. In addition, the results indicated that the bond index is sensitive to any shock or any unexpected change in exchange rate and interest rate and that these shocks manifest in the short term and stabilize in the long term.